Electronic Iran - The Cultural Politics of an Online Evolution - Akhavan, Niki (Rutgers University Press, 2021)
Electronic Iran introduces the concept of the Iranian Internet, a framework that captures interlinked, transnational networks of virtual and offline spaces. Taking her cues from early Internet ethnographies that stress the importance of treating the Internet as both a site and product of cultural production, accounts in media studies that highlight the continuities between old and new media, and a range of works that have made critical interventions in the field of Iranian studies, Niki Akhavan traces key developments and confronts conventional wisdom about digital media in general, and contemporary Iranian culture and politics in particular.